IMPLEMENTASI ALGORITMA FIRST COME FIRST SERVED PADA SISTEM ANTRIAN KLINIK UNTUK MENINGKATKAN KINERJA PELAYANAN (STUDI KASUS : KLINIK PRATAMA SEGER JOMBANG) - Luluk Maulida Maghfiroh; Mufarrihah, Iftitaahul; Lazulfa, Indana; Kristianto, Hery (Fakultas Teknologi Informasi, 2024)
Health care is an essential part of life. Because, a lot of societies need it every day, of course there are differentkinds of health care to adapt to the needs of the community. One of them is health care at the clinic. In itsservice, of course, Jombang’s clinic requires speed and accuracy so that the results of the service can satisfy thepatient. In practice, however, there are often long waiting times, due to a lack of waiting time management anduncertainty as to when the patient will be served. In order to help solve the problem, a solution was developed tocreate a website-based query system by applying the First Come First Served algorithm, which ensures that thepatient who first takes the query number will get the service before it is completed. Then, in this study, itinvolves collecting patient query data by observing the arrival time, the start time, and the completion time ofeach patient's service and the first come first served algoritm is responsible for setting the time of query. Theresults of the study show that the use of the First Come First Served algorithm in 20 data tracks gains an averageTA (Turnarround Time) of 73.05 minutes.Keywords: Queue, Clinic, First Come First Served, Service